DECK: an environment for parallel programming on clusters of multiprocessors - Barreto, Marcos; Ávila, Rafael; Oliveira, Fábio; Cassali, Ricardo; Navaux, Philippe (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41231, 2000)
As cluster-based architectures are becoming a well-established platform to the development and execution of parallel applications which demand for high performance, new requirements are imposed to the software used in such architectures. Within this context, we have developed DECK, an environment conceived to allow the development of parallel applications on top of this new architecture. This work presents the internal structure and the functionalities of DECK, as well as a performance evaluation of its two available implementations.